Hate Speech in Cyberspace: Fueling the Rejection of Rohingya Refugees in Indonesia - Fadhil, Haidar Masyhur; Rizkiyatul Imtyas (JURNAL PENELITIAN, 2024)
This research aims to trace and analyze how negative sentiments towards Rohingya refugees are disseminated on Social Media Platform X. This phenomenon is increasingly concerning as it involves not only negative sentiments but also the spread of hoaxes that can lead to discrimination and hatred. The study employs a qualitative approach with a descriptive-analysis method, focusing on content analysis of hate narratives emerging on Social Media Platform X. Collected data include comments, posts, and various forms of negative content targeting Rohingya refugees. I argue that hate speech towards Rohingya refugees tends to originate from anonymous fanbase accounts. The negative narratives from these accounts successfully shape public opinion and cultivate a xenophobic attitude among Indonesian netizens on Social Media Platform X. Furthermore, this hate speech contributes to the creation of a double standard between the issues of Palestine and Rohingya on Social Media Platform X, potentially influencing society's perception and attitude towards both issues.